Kontekstualisasi Pemaknaan Zawj dan Ba‘l Dalam al-Qur’an: Analisis Terhadap Qs. al-Baqarah [2]: 232 dan Qs. al-Nisā’ [4]:128 - Akbar, Ali; Malia Hayati, Safira; Yasir, Muhammad; Jamal, Khairunnas (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2022)
Abstract: This article aims to discuss the meaning of zawj and ba‘l in the Qur’an, as both terminologies, however, perceived to denote similar sense of meaning, namely husband, though the two words have different context of narratives. The verses addressed in this study are Qs. al-Baqarāh [2]: 232 and Qs. al-Nisā’ [4]: 128. By using contextual approach, namely ma‘nā-cum-maghzā, as framework of study, this article attempts to unveil the meaning of related concept above, mainly on its historical meaning, historical phenomenal significance, and dynamic phenomenal significance. Based on these three methods of analysis, this article argues that the significance (maghzā) contained in this verse are: first, the words of zawj and ba‘l are used in different contexts of ‘husband’. Second, the Qur’an views that women have the right to ‘choose and make decisions’ for their own life particularly related to their future marriage. Third, the Qur’an views men and women equally in household relations.